Prospects for the Botulinum Toxin Use in the Treatment of Children`s Strabismus. Review - E. Y. Markova; K. A. Dubrovina; G. V. Avakyants; E. A. Malayan (Oftalʹmologiâ)
The review presents information concerning the botulinum toxin use in the treatment of children`s strabismus; highlights aspects of the safety and the complications frequency. It contains information about the methods and doses of botulinum toxin injection, and also considers the cases of necessity of further surgery. There are several ways of introducing BTA: the traditional transconjunctival method of administration under the control of electromyography, used by most ophthalmologists, is not acceptable for treating pediatric patients, transconjunctivally into the subtenon space 10 mm from the limbus into the projection zone of the medial rectus muscle using a 1.0 ml tuberculin syringe with 27G needle, introduction to the muscle with the opening of the conjunctiva, which is safer, is carried out under complete visual control and with the release of extraocular muscle. According to the domestic and foreign literature data we can conclude that the injection of botulinum toxin may be an alternative or complement to surgical techniques, injection of botulinum toxin in the treatment of strabismus in children may be an alternative or complement to surgical and pleopto-orthopto-diploptic correction methods, although not in all clinical cases. The treatment approach of such patients should be comprehensive. There are reports that BoNT-A reduces eye deflection in more than 50 % of patients and provides satisfactory long-term results in infants and children. The average safe dose for Botox is 1-3 units for the muscle. The frequency of complications increases with higher doses (especially> 10 units) and with the transconjunctival route of administration without electromyographic control. This clinical example illustrates the effectiveness of botulinum toxin for the non-concomitant strabismus treatment.